A low cost dural closure simulation model for tomorrow's spinal neurosurgeons. (4th May 2019) - Ferguson, Deborah; Agyemang, Kevin; Barrett, Christopher; Mathieson, Calan
Abstract: Introduction: We present a low cost model that can be used to improve a trainee's skills in spinal dural closure. Development of microsurgical skills in a simulated environment provides a safe environment in which patients are protected. We argue that this is likely to improve the quality of dural closure, especially for surgeons early in their training and may lead to a commensurate reduction in post-operative CSF leak. Method: In our model, two consultant spine surgeons assessed the ability of participants to close the spinal dura. Participants were scored both quantitatively (time taken to complete the task) and qualitatively under the category of "surgical performance"- assessed by video and inspection of the closed dural substitute. Results: The cohort under assessment included senior and newly appointed consultants, clinical fellows and thirteen specialty trainees. 10 trainees were assessed a second time and a significant majority improved on both domains: 8 (80%) were faster on their second attempt; surgical performance scores also improved in the majority of trainees (90%). Conclusion: Our results, albeit with small numbers, show that a large proportion of trainees improve with practice with a reduction in overall task time and an improvement in surgical performance. Our model is cost-effective and easy to reproduce: simulation need not be an expensive exercise. This study further validates the use of simulation in modern neurosurgical training.